Satisfaction Level of using Web-Based Media in Optimizing Guidance and Counseling Services for Students of Class XI IPA 1 SMA YWKA Palembang - Nurullah, Muhammad Agung; Sucipto, Sigit Dwi; Rozzaqyah3, Fadhlina; Wisma4, Nur (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
This study was conducted to determine the level of satisfaction of using web-based media in optimizing guidance and counseling services. In this study using a quantitative approach with a descriptive method. The population in this study were students of class XI IPA 1 which amounted to 32 students and the sample of this study amounted to 32 students using totally sampling. The data collection technique uses a satisfaction with the use of web-based media. The results showed that the satisfaction level of using web-based media in optimizing guidance and counseling services was 19% in the low category, 69% in the medium category, and 13% in the high category. So it can be concluded that the level satisfaction of using web-based media in optimizing guidance and counseling services is in the medium category.